Taxonomical analysis of agaricoid basidiomycetes from the National Park «Belovezhskaya Pushcha» in MSK-F herbarium collections - Antonovich, Anna O. (Experimental Biology and Biotechnology, 2023)
The herbarium is the most representative repository of various types of fungi collected in different phytocenoses, thanks to which one gets an idea of the diversity and geographical distribution of most taxa of the mycobiota of certain territory. The lists of species created on the basis of the herbarium make it possible to track the dynamics of mycological communities and draw conclusions about the direction of development of the forest phytocenosis. In the MSK-F herbarium, 283 species of basidial macromycetes (including 12 varieties and 1 form) growing in the National Park «Belovezhskaya Pushcha» were identified. The most represented by the number of species is the order Agaricales. The herbarium MSK-F contains 215 species of agaricoid basidiomycetes from 23 families belonging to this order and forming the basis of the mycobiota of park. The most numerous families in terms of the number of species are represented by the families Russulaceae (40 species), Cortinariaceae (30 species), Mycenaceae (27 species), Agaricaceae (24 species) and Tricholomataceae (20 species).
Keywords: agaricoid basidiomycetes; mycobiota; protected area; National Park «Belovezhskaya Pushcha»; species composition; taxonomy